Kontribusi ‘Aisyiyah terhadap Peningkatan Kualitas Hidup Perempuan dalam Perspektif Islam Berkemajuan - Devita Nur Aizsya; Siti Julaiha; Dina Mardiana (Ameena Journal, 2026)
‘Aisyiyah was founded in 1917 as the first Islamic women’s organization in Indonesia advocating for women’s rights and education amid a patriarchal culture. The organization integrates spiritual, intellectual, and social values within the framework of Progressive Islam. This study aims to examine the contribution of ‘Aisyiyah to improving women’s quality of life in education and empowerment. The study employed a qualitative method using a Systematic Literature Review (SLR) approach based on PRISMA 2020 guidelines. Data were collected from six scientific articles and official documents of ‘Aisyiyah and Muhammadiyah. The findings show that ‘Aisyiyah contributes to education, gender equality, economic empowerment, spiritual leadership, and gender advocacy. ‘Aisyiyah established schools from the colonial era to higher education institutions, as well as cooperatives, hospitals, and economic training programs to support women’s independence. Spiritual leadership training also improved members’ understanding and skills. This study concludes that ‘Aisyiyah has successfully fostered independent, educated, and empowered women while affirming that Islam can serve as a foundation for women’s empowerment.